2016
DOI: 10.1063/1.4954697
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear model for magnetocapacitance effect in PZT-ring/Terfenol-D-strip magnetoelectric composites

Abstract: In previous works, most of them employ a linear constitutive model to describe magnetocapacitance (MC) effect in magnetoelectric (ME) composites, which lead to deficiency in their theoretical results. In view of this, based on a nonlinear magnetostrictive constitutive relation and a linear piezoelectric constitutive relation, we establish a nonlinear model for MC effect in PZT-ring/Terfenol-D-strip ME composites. The numerical results in this paper coincide better with experimental data than that of a linear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In order to improve the magnetically tunable MC effect, Wang et al investigated the giant magnetocapacitance effect of a Terfenol-D/PZT/Terfenol-D composite at a high applied magnetic field of 1.5 kOe [ 20 ]. Zhang et al studied a nonlinear model for the magnetocapacitance effect of PZT-ring/Terfenol-D-strip composites and discussed the effect of boundary conditions on magnetocapacitance [ 21 , 22 ]. However, Terfenol-D possesses a quite low relative magnetic permeability (μ r = 10) and mechanical brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the magnetically tunable MC effect, Wang et al investigated the giant magnetocapacitance effect of a Terfenol-D/PZT/Terfenol-D composite at a high applied magnetic field of 1.5 kOe [ 20 ]. Zhang et al studied a nonlinear model for the magnetocapacitance effect of PZT-ring/Terfenol-D-strip composites and discussed the effect of boundary conditions on magnetocapacitance [ 21 , 22 ]. However, Terfenol-D possesses a quite low relative magnetic permeability (μ r = 10) and mechanical brittleness.…”
Section: Introductionmentioning
confidence: 99%
“…ME composites are especially promising for tunable electrical component (resistors, capacitors, inductors, etc.) applications [ 11 , 12 , 13 , 14 ], among which E-field tunable inductors based on ME laminate composites have been widely studied recently. Fang et al have reported the electric-field-induced inductance change for a heterogeneous composite consisting of a PZT bar embedded in a MnZn ferrite ring [ 15 ].…”
Section: Introductionmentioning
confidence: 99%